MOLECULAR DYNAMICS STUDY OF SIZE DEPENDENCES OF MELTING AND CRYSTALLIZATION HEATS OF PLATINUM AND PALLADIUM NANOCLUSTERS - S.A. Vasilyev; A.A. Romanov; N.V. Vostrov; V.L. Skopich; K.G. Savina (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2019)
On the basis of the molecular dynamics results obtained by using the tight binding potential, the heats of melting, crystallization, and also the sublimation and evaporation heats of platinum and palladium nanoclusters were found. The obtained size dependences are linear if the inverse radius is chosen as an argument, which allows extrapolating the dependencies to the corresponding bulk phases and comparing with the tabulated values.